Parent Training for ADHD: No Generalization of Effects From Clinical to Neuropsychological Outcomes in a Randomized Controlled Trial. Issue 1 (January 2023) - Lambek, Rikke; Sonuga-Barke, Edmund J. S.; Lange, Anne-Mette; Carroll, Daniel J.; Daley, David; Thomsen, Per Hove
Objective: We examined whether neuropsychological function in ADHD can be improved by the New Forest Parenting Programme (NFPP), that combines standard parenting strategies with self-regulatory skills training, or predict ADHD and quality of life (QoL) treatment effects. Method: Participants were 93 medication-naive preschool children with ADHD (3–7 years) randomized to either NFPP ( n = 49) or treatment as usual (TAU; n = 44) in a recent randomized trial. Laboratory measures of executive function, reaction time variability, and delay of gratification were collected along with parent ratings of ADHD and QoL at baseline and post treatment. Ratings were collected again at 3-month follow-up. Results: NFPP did not improve neuropsychological function (compared to TAU), and baseline neuropsychological function did not predict treatment-related ADHD or QoL effects. Conclusion: Although NFPP includes a neuropsychological training element and has been shown to improve several clinical outcomes, it did not improve the neuropsychological functions it targets.